“Some Heraldic Propriety of Composition”: Solving the Mystery of the Origin and History of the Armorial Achievement of the County of Wellington, Ontario - Lofft, Jonathan (Ontario History)

(untitled) (The Ontario Historical Society, 2019)
This article documents the origins of the armorial achievement, the arms and crest, adopted by Wellington County in 1860. It compares amateur and authoritative revisions of the blazon of this achievement, and considers the connection between imperial toponym and heraldic emblem, that is, between name and arms, for the first time positively identifying the designer as fledgling celebrated Canadian heraldist Edward Marion Chadwick (1840-1921).